Discordance in reporting of maternal aggression: exploring differences by characteristics of children, mothers, and their environments - Kremer, Kristen P. (Child maltreatment, 2020)
This study investigated discordant reports of maternal aggression using the Fragile Families and Child Wellbeing Study (N = 1,606). Multinomial logistic regression models predicted discordant reports of hitting and shouting from child, mother, and environmental characteristics. Compared to dyads in which both mothers and children reported aggression, mothers with a college degree had higher child-only and mother-only reports of both hitting and shouting versus mothers with less than a high school diploma. High-income mothers had higher child-only reports of hitting, while families with past Child Protective Services involvement had higher child-only and mother-only reports of hitting. Additionally, children with lower reading test scores and whose fathers had history of incarceration had higher child-only reports of hitting. Families residing in neighborhoods for which mothers were scared to let children play outside also had higher child-only and mother-only reports of hitting and shouting.